Fostering Empathy through Museums - Gokcigdem, Elif M. (Rowman and Littlefield, 2016)
"Fostering Empathy through Museums features ten case studies with clear take-away ideas, and lessons learned by vividly illustrating a spectrum of approaches in the way museums are currently employing empathy, a critical skill that is relevant to personal, institutional, economical, or social progress, and will need to be better understood by any institution serving society. This book will help museum staff (from zoos, to historic house museums, to science, and art museums) and informal education specialists at all levels to better understand the multitude of ways that empathy can be employed and nurtured and might lead to improved systems designs, visitor's experiences, exhibitions, and educational programs that are engaging and that value human connection and emotions as a critical ingredient of the learning experience"--Provided by publisher